Smart adsorption systems: Combining electrospun PEI-PAN-GO membranes with deep learning models for real-time prediction and optimization of pollutant removal efficiency - Waqar Iqbal; Hongzhen Cai; Ahmed ElManawy; Xiangsheng Han; Mohammad Younas; Jiankang Zhang; Keyan Yang; Tohid Tavangar; Mashallah Rezakazemi (Chemical Engineering Journal, 2026)

Lignin enhanced thermal conductive wood-based phase change materials for passive building thermal management - Xu Huang; Jianing Zhang; Zhiqiang Qi; Wenyu Lu; Keyan Yang; Hongzhen Cai; Jibing Zhang (Chemical Engineering Journal, 2026)

Three-Dimensional Mineral Prospectivity Mapping by a Gradient Boosting-Based Integrated Learning Method with Data Representation Adaptability: A Case Study of the Haopinggou Gold Polymetallic Deposit, China - Mingjing Fan; Keyan Xiao; Li Sun; Nan Li; Yang Xu; Wenjie Li (Natural Resources Research, 2026)

Elevation dependence of vegetation phenology on the southeastern margin of the Tibetan Plateau - Tiantian Yang; Zheneng Hu; Wanxiong Zhang; Jingjing Wang; Zhongshi Zhang; Keyan Fang; Xin Zhou; Jie Zhou; Zhuoya Zhang; Zhengtang Guo (Science China Earth Sciences, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Tracing sources and ecological risks: seasonal-spatial variations of potentially toxic element (PTE) pollution in marine sediments of Beibu Gulf - Zihan Bi; Yao Guan; Linshen Yang; Rongtao Ou; Yilu Gu; Huihua Wei; Xin Liu; Zezhuang Liu; Liping Tian; Keyan Xiao; Siyong Quan; Xuya Peng; et al. (Marine Pollution Bulletin, 2026)

Lignin-intercalated WS2 with synergistic adsorption for efficiency lead removal - Baohua Liu; Xiangsheng Han; Keyan Yang; Jiankang Zhang; Hongzhen Cai (Bioresource Technology, 2026)

Multidecadal modulation of multi-year El Niño events over the past millennium - Shuheng Lin; Keyan Fang; Hao Wu; Hanjie Fan; Feifei Zhou; Jinbao Li; Kaiqiang Deng; Hans W. Linderholm; Song Yang (Science China Earth Sciences, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

Framework for short-term hydropower cascade–station–unit integrated multi-objective scheduling: Considering unit safety and economic efficiency - Jingwei Huang; Hui Qin; Xu Yang; Keyan Shen; Huaming Yao; Xinyu Chang; Gaoge Li; Yuan Gao (Journal of Hydrology, 2025)

A scalable photovoltaic-type photoelectrotrophic denitrification reactor for selective conversion nitrate to nitrogen via isolating reactive oxygen species - Man Chen; Keyan Chen; Yang Li; Youming Diao; Yixi Li; Raymond Jianxiong Zeng; Shungui Zhou (Chemical Engineering Journal, 2025)

A novel reservoir dispatching rules extraction framework based on hybrid embedding informer - Shuai Liu; Hui Qin; Zhengyang Tang; Keyan Shen; Xu Yang; Zhiwei Zheng; Yuhua Qu; Zhiwei Jia (Journal of Hydrology, 2024)

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

Reactive transport numerical modeling of intermediate sulfidation epithermal deposit: A case study of Haopinggou Ag-Au-Pb-Zn deposit, Henan province, China - Cheng Chang; Keyan Xiao; Guanhong Feng; Li Sun; Junsheng Yang (Journal of Geochemical Exploration, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Deep multimodal fusion for 3D mineral prospectivity modeling: Integration of geological models and simulation data via canonical-correlated joint fusion networks - Yang Zheng; Hao Deng; Jingjie Wu; Shaofeng Xie; Xinyue Li; Yudong Chen; Nan Li; Keyan Xiao; Norbert Pfeifer; Xiancheng Mao (Computers & Geosciences, 2024)

Effect of staged thawing assisted antifreeze protein on quality of repeatedly freeze-thawed minced pork - Ying Zhou; Keyan Jing; Chuankang Jia; Rongrong Mao; Baoxue Zhang; Bin Yang; Ci Yuan; Jun Qi; Guoyuan Xiong; Chunhui Zhang; Zhangguo Gao; Wei Xiong (Food Control, 2024)

Extracting operation rule of cascade reservoirs using a novel framework considering hydrometeorological spatiotemporal information based on artificial intelligence models - Wei Fang; Hui Qin; Keyan Shen; Xin Yang; Yuqi Yang; Benjun Jia (Journal of Cleaner Production, 2024)

Comparing multiple machine learning models to investigate the relationship between urban morphology and PM2.5 based on mobile monitoring - Jianfeng Zhang; Yang Wan; Meng Tian; Hao Li; Keyan Chen; Xuesong Xu; Lei Yuan (Building and Environment, 2024)

ZYY-B-2, a novel ALK inhibitor, overcomes resistance to ceritinib by inhibiting P-gp function and induces apoptosis through mitochondrial pathway in ceritinib-resistant H2228 cells - Ying Gao; Tong Liu; Jingang Liu; Yuying Yang; Keyan Sun; Zengqiang Li; Xin Zhai; Daiying Zuo (Chemico-Biological Interactions, 2023)

Recovery of bio‑sulfur and metal resources from mine wastewater by sulfide biological oxidation-alkali flocculation: A pilot-scale study - Xin Hu; Hong Yang; Xiaoyue Fang; Tongyu Shi; Keyan Tan (Science of The Total Environment, 2023)

Rapid expansion of wetlands on the Central Tibetan Plateau by global warming and El Niño - Yang Li; Zhengyang Hou; Liqiang Zhang; Changqing Song; Shilong Piao; Jintai Lin; Shushi Peng; Keyan Fang; Jing Yang; Ying Qu; Yuebin Wang; Jingwen Li; et al. (Science Bulletin, 2023)

In-situ construction of BiOBr/Bi2WO6 S-scheme heterojunction nanoflowers for highly efficient CO2 photoreduction: Regulation of morphology and surface oxygen vacancy - Jiaming Wu; Keyan Li; Siyu Yang; Chunshan Song; Xinwen Guo (Chemical Engineering Journal, 2023)

Thiol “click” chromene mediated cascade reaction forming coumarin for in-situ imaging of thiol flux in drug-induced liver injury - Yutao Yang; Keyan Zhou; Ming Ma; Hongmei Liu; Ming Jin; Caixia Yin; Shuxiang Wang; Jinchao Zhang (Chemical Engineering Journal, 2023)

Metabolism balance regulation for squalene production by disturbing triglyceride (TAG) synthesis in Schizochytrium sp. - Ran Duan; Xueshan Pan; Keyan Li; Qinghua Yang; Xiaowen Cui; Yayun Zheng; Yinghua Lu; Chuanyi Yao; Xueping Ling (Algal Research, 2023)

Mineral Prospectivity Mapping based on Isolation Forest and Random Forest: Implication for the Existence of Spatial Signature of Mineralization in Outliers - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Hantao Wei; Fan Yang; Zhenghui Chen; Nan Li; Jie Xiang (Natural Resources Research, 2022)

Overestimated gains in water‐use efficiency by global forests - Xiao Ying Gong; Wei Ting Ma; Yong Zhi Yu; Keyan Fang; Yusheng Yang; Guillaume Tcherkez; Mark A. Adams (Global Change Biology, 2022)
Increases in terrestrial water‐use efficiency (WUE) have been reported in many studies, pointing to potential changes in physiological forcing of global carbon and hydrological cycles. However, gains in WUE are of uncertain magnitude over longer (i.e. >10 years) periods of time largely owing to difficulties in accounting for structural and physiological acclimation. 13 C signatures (i.e. δ 13 C) of plant organic matter have long been used to estimate WUE at temporal scales ranging from days to centuries. Mesophyll conductance is a key uncertainty in estimated WUE owing to its influence on diffusion of CO 2 to sites of carboxylation. Here we apply new knowledge of mesophyll conductance to 464 δ 13 C chronologies in tree‐rings of 143 species spanning global biomes. Adjusted for mesophyll conductance, gains in WUE during the 20th century (0.15 ppm year −1 ) were considerably smaller than those estimated from conventional modelling (0.26 ppm year −1 ). Across the globe, mean sensitivity of WUE to atmospheric CO 2 was 0.15 ppm ppm −1 . Ratios of internal‐to‐atmospheric CO 2 (on a mole fraction basis; c i / c a ) in leaves were mostly constant over time but differed among biomes and plant taxa—highlighting the significance of both plant structure and physiology. Together with synchronized responses in stomatal and mesophyll conductance, our results suggest that ratios of chloroplastic‐to‐atmospheric CO 2 ( c c / c a ) are constrained over time. We conclude that forest WUE may have not increased as much as previously suggested and that projections of future climate forcing via CO 2 fertilization may need to be adjusted accordingly.

Geochemically Constrained Prospectivity Mapping Aided by Unsupervised Cluster Analysis - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Zhenghui Chen; Nan Li; Hantao Wei; Jie Xiang; Li Sun; Yang Xu (Natural Resources Research, 2021)

Host-induced gene silencing of brown planthopper glutathione S-transferase gene enhances rice resistance to sap-sucking insect pests - Jun Yang; Xiao-Qin Sun; Keyan Zhu-Salzman; Qing-Ming Qin; Hui-Qiang Feng; Xiang-Dong Kong; Xu-Guo Zhou; Qing-Nian Cai (Journal of Pest Science, 2021)

Data-driven Mineral Prospectivity Mapping by Joint Application of Unsupervised Convolutional Auto-encoder Network and Supervised Convolutional Neural Network - Shuai Zhang; Emmanuel John M. Carranza; Hantao Wei; Keyan Xiao; Fan Yang; Jie Xiang; Shihong Zhang; Yang Xu (Natural Resources Research, 2021)

3D Mineral Prospectivity Mapping Based on Deep Metallogenic Prediction Theory: A Case Study of the Lala Copper Mine, Sichuan, China - Keyan Xiao; Jie Xiang; Mingjing Fan; Yang Xu (Journal of Earth Science, 2021)

Uncertainty Visualisation of a 3D Geological Geometry Model and Its Application in GIS-Based Mineral Resource Assessment: A Case Study in Huayuan District, Northwestern Hunan Province, China - Nan Li; Cangbai Li; Wenkai Chu; Keyan Xiao; Weihan Tao; Xianglong Song; Rui Cao; Yang Xu; Mingjing Fan (Journal of Earth Science, 2021)

Reinvestigation of the substrate specificity of a reverse prenyltransferase NotF from Aspergillus sp. MF297-2 - Keyan Yang; Shu-Ming Li; Xiaoqing Liu; Aili Fan (Archives of Microbiology, 2020)

Maximum Entropy and Random Forest Modeling of Mineral Potential: Analysis of Gold Prospectivity in the Hezuo–Meiwu District, West Qinling Orogen, China - Shuai Zhang; Keyan Xiao; Emmanuel John M. Carranza; Fan Yang (Natural Resources Research, 2019)

Moisture increase in response to high-altitude warming evidenced by tree-rings on the southeastern Tibetan Plateau - Jinbao Li; Jiangfeng Shi; David D. Zhang; Bao Yang; Keyan Fang; Pak Hong Yue (Climate Dynamics, 2017)

Does Fluoride Affect Serum Testosterone and Androgen Binding Protein with Age-Specificity? A Population-Based Cross-Sectional Study in Chinese Male Farmers - Leizhen Duan; Jingyuan Zhu; Keyan Wang; Guoyu Zhou; Yuejin Yang; Liuxin Cui; Hui Huang; Xuemin Cheng; Yue Ba (Biological Trace Element Research, 2016)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Is APOE $\boldsymbol{ε}$ 3 a favourable factor for the longevity: an association study in Chinese population - JIE FENG; LEI XIANG; GANG WAN; KEYAN QI; LIANG SUN; ZEZHI HUANG; CHENGUANG ZHENG; ZEPING LV; CAIYOU HU; ZE YANG (Journal of Genetics, 2011)

The impacts of permafrost change on NPP and implications: A case of the source regions of Yangtze and Yellow Rivers - Yiping Fang; Dahe Qin; Yongjian Ding; Jianping Yang; Keyan Xu (Journal of Mountain Science, 2011)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Reconstructed droughts for the southeastern Tibetan Plateau over the past 568 years and its linkages to the Pacific and Atlantic Ocean climate variability - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Nicole Davi (Climate Dynamics, 2010)

Drought reconstruction in the Qilian Mountains over the last two centuries and its implications for large-scale moisture patterns - Wenhuo Liu; Xiaohua Gou; Meixue Yang; Yong Zhang; Keyan Fang; Tao Yang; Liya Jin (Advances in Atmospheric Sciences, 2009)